Identification of a novel, MSC-induced macrophage subtype via single-cell sequencing: implications for intervertebral disc degeneration therapy - Koroth, Jinsha; Chitwood, Casey; Kumar, Ramya; Lin, Wei-Han; Reves, Benjamin T.; Boyce, Todd; Reineke, Theresa M.; Ellingson, Arin M.; Johnson, Casey P.; Stone, Laura S.; Chaffin, Kimberly C.; Simha, Narendra K.; et al. (Frontiers in Cell and Developmental Biology, 2024)
Intervertebral disc (IVD) degeneration is a common pathological condition associated with low back pain. Recent evidence suggests that mesenchymal signaling cells (MSCs) promote IVD regeneration, but underlying mechanisms remain poorly defined. One postulated mechanism is via modulation of macrophage phenotypes. In this manuscript, we tested the hypothesis that MSCs produce trophic factors that alter macrophage subsets. To this end, we collected conditioned medium from human, bone marrow-derived STRO3+ MSCs. We then cultured human bone marrow-derived macrophages in MSC conditioned medium (CM) and performed single cell RNA-sequencing. Comparative analyses between macrophages cultured in hypoxic and normoxic MSC CM showed large overlap between macrophage subsets; however, we identified a unique hypoxic MSC CM-induced macrophage cluster. To determine if factors from MSC CM simulated effects of the anti-inflammatory cytokine IL-4, we integrated the data from macrophages cultured in hypoxic MSC CM with and without IL-4 addition. Integration of these data sets showed considerable overlap, demonstrating that hypoxic MSC CM simulates the effects of IL-4. Interestingly, macrophages cultured in normoxic MSC CM in the absence of IL-4 did not significantly contribute to the unique cluster within our comparison analyses and showed differential TGF-β signaling; thus, normoxic conditions did not approximate IL-4. In addition, TGF-β neutralization partially limited the effects of MSC CM. In conclusion, our study identified a unique macrophage subset induced by MSCs within hypoxic conditions and supports that MSCs alter macrophage phenotypes through TGF-β-dependent mechanisms.